MAKING DYE SENSITIZED SOLAR CELL (DSSC) USING GMR AS SUBSTRACT AND PURPLE SWEET POTATO EXSTRACT (Ipomoea batatas L) AS A D DYE SENSITIZER - Utami Oktavia; Hary Sanjaya (Departemen Kimia FMIPA UNP, 2019)
Dye Sensitized Solar Cell (DSSC) is a third generation photovoltaic cell that configures visible light into electrical energy. This study aims to make DSSC using GMR as substrate with spin coating gel solvents and natural dyes from purple sweet potato (Ipomoea batatas L). From testing the purple sweet potato is known to contain anthocyanin compounds in testing using FTIR and has a maximum wavelength of 525 nm in testing Uv-Vis. From the results of the calculation of efficiency with immersion obtained at a concentration of 50% the efficiency is 0.19%, while the variation in immersion time is 5 hours of efficiency 0.72%.